Draft Annual Plan 1988-89 Volume : II General Areas Government of Assam - Planning Commission (Planning Commission, 1987)
The objective of 7th Plan is to achieve self-sufficiency in rice production, reduce the deficit of other food-grains to the extent possible and also to take up Programmes for argument ting the production of Oil-seeds and other commercial and horticultural crops. The Seventh Plan-allocation for Agriculture excluding 16.75 crores for assistance to Small and Marginal fanners is fixed at Rs, 122.10 crore of which a sum of Rs. 31.46 crore has been allotted for -the year, 1986-87. The Plan allocation for, 1987-88 is 3359 crores.
Government of Assam
Planning and Development Department
Keywords: Crop Husbandry; Agricultural Research Education; Other Agricultural Programme Marketing; Soil & Water Conservation Plan; Animal Husbandry; Dairy Development; Forestry & Wild life; Investee in Agricultural It Financial Institutions; Fool; Storage & Warehousing; Special Programme for Rural; Development; Interface Rural Development Programme; Rural Employment; National Rural Employment Programme; Integrated Rural Energy Programme